The three-dimensional growth of traumatic Intracerebral Hemorrhage in patients with abnormal coagulation - Rossmann, Jakob; Falter, Johannes; Höhne, Julius; Hohenberger, Christoph; Bründl, Elisabeth; Schmidt, Nils Ole; Schebesch, Karl-Michael; Bele, Sylvia (Journal of Neurological Surgery Part A: Central European Neurosurgery)
Background and purpose: The goal of the present study was to compare the volumetric three-dimensional growth of traumatic intracerebral hemorrhage (tICH) in patients with and without abnormal coagulation and question the necessity to perform repeated CT scans in all those patients. Methods: We retrospectively analysed CT-Scans from 50 patients with traumatic ICH. Abnormal coagulation was defined by the results of standard coagulation tests at admission including Factor XIII. The three-dimensional size of the hemorrhage was measured at admission, within 48 hours and 2 weeks. Results: Growth of the ICH was detected in 56 % of the patients. In the group with normal coagulation out of 30 patients, growth could only be detected in 10 (33.34 %) whereas in the abnormal coagulation group increased ICH volume occurred in 18 of 20 patients (90 %). The mean growth was 3.46 ml [95 % CI: +/- 2.99 ml] and varied from 0,1 ml [95 % CI: +/- 1.57] in the normal coagulation group to 8.52 ml [95 % CI: +/- 6.67 ml] in the coagulation disorder group. Conclusion: This study demonstrates the need to perform repeated CT scans in patients with coagulation disorders since patients with tICH and coagulation abnormalities are likely to experience substantial growth of the hemorrhage.